Understanding carbon nanoparticle transport in saturated porous media: the influence of dissolved organic matter - Gilkerson, Tyler, author; Sanford, William, advisor; Li, Yan, committee member; Ronayne, Michael, committee member (Colorado State University. Libraries, 2020)
Nanoparticles (NPs), or objects with all dimensions between 1 nanometer (nm) and 100 nm, are ubiquitous in atmospheric, aquatic, and terrestrial settings. The ability to engineer NPs and utilize their unique size-dependent physicochemical properties has resulted in the rise of nanotechnology as a prominent component of twenty-first century research and industry. Engineered nanoparticles (ENPs) commonly reach groundwater systems after being released to the environment as byproducts of various human goods and activities or agents of groundwater remediation. While ENPs are released at a significant rate, the transport mechanisms controlling their fate are poorly understood. Furthermore, some ENPs are toxic and capable of facilitating contaminant transport and bioavailability. Evaluating the ways in which ENPs are transported in groundwater is critical to effectively managing and regulating their release to and removal from natural systems. A NP with characteristics of an ideal groundwater tracer would enable powerful investigations of NP fate and transport processes in saturated porous media. Similar to applied conservative solute tracers, this NP could also be used to estimate aquifer and groundwater flow parameters. Recent studies indicate engineered carbon nanoparticles (CNPs) are ideal groundwater tracer candidates. With diameters from 2 nm to 5 nm, CNPs are nearly spherical carbon cores functionalized with a fluorescent coating. Additionally, these NPs are nontoxic, environmentally benign, highly hydrophilic, inexpensive, easily synthesized, and conveniently detected at low concentrations. Owing to their size, stability, and near-zero zeta potential, CNPs are transported conservatively and mostly unimpaired in saturated porous media under diverse environmental conditions (e.g. dual-porosity and positively charged sediment; high temperatures, pressures, and salinities; and alongside other ENPs and common solute tracers). Nonetheless, CNP transport in natural settings cannot be adequately understood without evaluating the influence of dissolved organic matter (DOM). This study executed four one-dimensional column experiments to investigate the influence of DOM on CNP transport in homogeneous coarse-grained silica sand. To compare CNP transport to that of a conservative solute tracer, CNPs were transported alongside bromide (Br) in each column experiment. Solution pHs of 4 and 7 were each maintained for two experiments to further evaluate the influence of DOM. Breakthrough curves (BTCs) were generated from effluent samples and analyzed via temporal moment methods (TMMs) and inverse modeling using the CXTFIT 2.1 code. These analyses enabled estimation of CNP and Br mass recovery and transport parameters such as velocity, retardation, and dispersion. Such estimates indicated that CNP transport and Br transport were similar and mostly conservative under all experimental conditions. However, while apparently enhanced by DOM, CNP transport was slightly retarded by reversible equilibrium and nonequilibrium adsorption to silica sand in all experiments. These findings generally agree with previous studies suggesting CNPs will transport conservatively in natural groundwater systems. While CNP transport is slightly impaired relative to Br under these experimental conditions, this research suggests CNPs could be used to elucidate how less-mobile nanoscale objects are transported in saturated porous media. Therefore, CNPs are tentatively regarded as ideal NP tracers.
Keywords: dissolved organic matter; hydrogeology; tracer; groundwater; carbon nanoparticle; particle transport